The prevalence and associated factors of tooth wear amongst adults seeking treatment in the Faculty of Dentistry, University Malaya - Al-Ani, Bilal Zuhair Nafea (2019)
Tooth wear of all patterns, like erosion, abrasion and/or attrition is a growing concern amongst dentist and community. Generally, the prevalence of tooth wear amongst all age group young adults, adult and elderly has significantly increased in recent years. The aim of the current study is to determine the prevalence of each type of tooth wear, evaluate the associated aetiological risk factors for such condition, as well to detect the severity of tooth wear in a group of participants who were seeking treatment in the Faculty of Dentistry, University of Malaya, Kuala Lumpur, Malaysia. The hypothesis state that there is a high prevalence of tooth wear for all subdivisions (erosion, abrasion and attrition) amongst adult with the associated risk factors that affect the longevity of teeth. In this study, 384 individuals who visited the Faculty of Dentistry, University of Malaya to seek treatment were involved. Subjects were 246 males and 138 females aged 20 to 65 years old. The researcher used the previously validated questionnaire and the clinical examination sheet based on Smith and Knight Tooth Wear Index 1984. SPSS program was used in the analysis of data. The results showed that the prevalence of tooth wear is high (95%) and the most prevalent type of tooth wear is dental attrition (82%), followed by dental erosion (52%), while dental abrasion is the lowest prevalent type (43%). In addition, age is significantly related to tooth wear. Alcohol consumption and tobacco smoking have significantly affected dental tissues and increased the incidenceof tooth wear. Oral hygiene practice is highly related to dental abrasion. Moreover, bruxism shows a significant relationship with dental attrition. Overall, the majority of the affected tooth surfaces scored grade 1 based on Smith and Knight Tooth Wear Index (71%). Tooth wear grade 2 are scored (26%) and the remaining 3% were scored as grade 3 and 4. Based on this study, the prevalence of tooth wear was high (95%) amongst the adults attending the Faculty of Dentistry, University of Malaya and dental attrition was the most prevalent type of tooth wear.